Frontispiece: Covalency in Actinide Compounds. Issue 19 (2nd April 2021) - Pace, Kristen A.; Klepov, Vladislav V.; Berseneva, Anna A.; zur Loye, Hans‐Conrad
Abstract : This frontispiece illustrates two ways of achieving a higher degree of covalency in actinide compounds, one employs orbital energy degeneracy and the other—orbital overlap between the 5f and ligand orbitals. For more information see the Concept article by V. V. Klepov, H.‐C. zur Loye et al. on page 5835 .